2018
DOI: 10.1002/app.46446
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical enhancement of amine‐functionalized TiO2 reinforced polyimine composites

Abstract: Polyimine vitrimers are known for their malleability, which endows these materials with properties such as self‐healing, recycling, and reshaping. To enhance the mechanical properties of the polyimine vitrimers, composites were fabricated by incorporating amine‐functionalized TiO2 microspheres (amTiO2MS) into polyimine matrix. The pure polyimine matrix and polyimine composites hybridized with TiO2 microspheres (TiO2MS) without surface modification were also obtained and examined as the controls in characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 75 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…In addition, the strength and modulus of the single-layer PI-Mica film are superior to those of other PI-based composite films (Figure 2e and Table S1, Supporting Information). [15,28,[31][32][33][34][35][36][37][38][39][40][41] The improvement in the mechanical properties of the final singlelayer PI-Mica film is mainly attributed to its ordered and uniform layered microstructure. [42,43] However, we found that after tensile failure in single-layer PI-Mica films, many of the mica nanosheets were pulled out from the PI matrix at the fracture location, forming prominent trapezoidal structures and irregular deflections (Figure S4b-f, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the strength and modulus of the single-layer PI-Mica film are superior to those of other PI-based composite films (Figure 2e and Table S1, Supporting Information). [15,28,[31][32][33][34][35][36][37][38][39][40][41] The improvement in the mechanical properties of the final singlelayer PI-Mica film is mainly attributed to its ordered and uniform layered microstructure. [42,43] However, we found that after tensile failure in single-layer PI-Mica films, many of the mica nanosheets were pulled out from the PI matrix at the fracture location, forming prominent trapezoidal structures and irregular deflections (Figure S4b-f, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The vitrimer concept was first demonstrated on epoxy networks. Notwithstanding the existence of alternative chemistry, the epoxy route remains the straightforward option for transfer of the vitrimer concept in structural composite applications. Proof that epoxy vitrimers are a suitable matrix for FRP composites has been given several times: , Chabert et al produced vitrimer matrices with exchangeable ester links and a T α value > 100 °C .…”
Section: Introductionmentioning
confidence: 99%